Educational policies about text-books in contemporary Spain: origin, evolution and present state - de Puelles Benítez, Manuel (Avances en Supervisión Educativa, 2007)
Text-books are versatile objects: a tool for educational purposes, a cultural item derived from different conceptions, a commercial good connected to the publishing houses domain, and a useful means to transmit values, since text-books not only widespread knowledge but also contain certain values which in a self-evident or concealed way are intrinsic to them. This is a feature that educational policies have never left aside nor have been indifferent to. Text-books are also, in a higher or lower degree, an ideological product which has been a favourite object in educational policies in every country.In different periods of time in the History of Spain, freedom to choose the most suitable text-book has been a token of policies in favour of rights and liberties.